The Correlation Between Knowledge Level and Perception with the Community Stigma on PLWH in Pandowoharjo Village, Sleman - Finnajakh, Aunana; Meilani, Niken; Setiyawati, Nanik (Proceeding International Conference on Science and Engineering, 2020)
From the number of years HIV / AIDS cases are increasing. In Indonesia, the number of people living with HIV in 2016 was 620,000 (530,000-730,000). Yogyakarta Special Region (DIY) in 2017 was the 12th rank as the province with the most HIV-AIDS patients in Indonesia. Sleman Regency was the regency with the highest HIV / AIDS patients in DIY. Stigma causes HIV prevention and health services to be less effective.